Examining the Effect of Tablets to Enhance Essay Writing Competencies of Primary School Students - Lhendup, Tshewang; Jimba, Ugyen (International Journal of Humanities and Education Development (IJHED), 2021)
Writing is one of the most important aspects of any standardized test all over the world. Much emphasis is hence placed on improving writing standards in schools and other forms of educational institutions. With improved technological infrastructure, digital devices such as Tablets are increasingly being used in the teaching and learning process. This study aimed to explore the effects of Tablets in supporting grade VI students to enhance narrative essay writing skills. This particular study utilised 14 sessions comprising of 50 minutes each in both control and experimental situations. The control group is a simulation of a face-to-face teaching scenario, while the students in the experimental group replicated the non-contact teaching set-up. A total of 49 grade VI students from two primary schools selected using a convenience sampling technique participated in the study. The data for the study was collected through written tests both before and after the intervention. The analyses were conducted using descriptive statistics and t-tests. The results showed that the differences in writing scores between control and experimental groups were statistically significant. Based on this finding, the use of Tablets in teaching essay writing may be considered helpful for primary schools irrespective of the school location.